Growth analysis of fenugreek (Trigonella foenum-graecum L.) under various levels of farmyard manure and phosphorus - Singh, K D Khiriya, R S Sheoran, B P (Journal of Spices and Aromatic Crops, 2001)
Field investigations were carried out during winter (rabi) season of 1996-97 and 1997-98 to study the effect of different levels of farmyard manure and phosphorus on growth of two fenugreek genotypes in sandy loam soils. The results indicated that genotype NLM was significantly superior to HM-65 in terms of plant height, LAI, LAD CGR and dry matter accumulation at all stages of crop growth, except at 30 DAS. These growth parameters in the genotype NLM resulted in higher seed yield. Plant height, LAI, LAD, CGR and dry matter accumulation were significantly higher with increase of FYM upto 15 t ha-1 at all stages of crop growth, except at 30 DAS. Seed yield was also enhanced significantly with the FYM up to 15 t ha-1. Increasing levels of phosphorus upto 40 kg ha-1 significantly increased the growth parameters and yield of fenugreek.